184k views
2 votes
Find (g•f)(3) f(x) = 3x-2
g(x) = x^2

User Antoneil
by
5.8k points

1 Answer

1 vote

Answer:

For this case, the first thing we must do is the composition of functions.

We have:

f (x) = 3x-2

g (x) = x ^ 2

(gOf) (x) = (3x-2) ^ 2

We now evaluate the function:

(gOf) (3) = (3 * (3) -2) ^ 2

(gOf) (3) = (9-2) ^ 2

(gOf) (3) = (7) ^ 2

(gOf) (3) = 49

Answer:

(g.f) (3) = 49

Explanation:

User Redox
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.